Review: interactions between microplastics and the gastrointestinal microbiome - Julia Eichinger; Marco Tretola; Jana Seifert; Daniel Brugger (Italian Journal of Animal Science)
Plastics are ubiquitous materials in our daily lives, but their inadequate disposal has led to the widespread distribution of their micro- and nanoparticles in various ecosystems. Their detection in feed and food, as well as in livestock and human stool samples, strongly suggests a continuous circulation in the feed and food chain. The ability of plastic particles to penetrate the intestinal barrier determines their accumulation in the body and in food of animal origin. The gastrointestinal (GI) microbiome, whose fermentation activity can influence the particle size distribution of certain plastic materials and which is known to modulate the permeability of the intestinal barrier, may be a critical hub in this transfer. This review attempts to summarise research efforts to date on the interaction between microplastics (MPs) and the GI microbiome of humans, mice, chickens and aquatic animals. We have analysed the state of knowledge and identified future avenues for targeted research approaches to answer open questions regarding the interaction of plastic particles with the GI microbiome, which may help to develop predictive models for the accumulation of plastic particles from feed and food in the body and animal products, respectively.HIGHLIGHTS Microplastics (MPs) influence the gastrointestinal (GI) microbiome. The microbiome may facilitate microplastic breakdown. This may influence the size distribution of plastic particles and their potential to penetrate the intestinal barrier.